An «author’s signs» from style in instrumental music by Hennady Liashenko - Denysenko-Sapmaz, Maryna (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2018)
Relevance of the study. Individual senses from instrumental music by the wellknown Ukrainian composer Hennady Liashenko, are founding with a such difficulties: the contra versions between scientifically and memorial types of analyze in this study are looking like a «translations». Because the topic of stylish, which rule by mental and world viewing specifies of his composer’s meaning, the main attentions must paying to his spirit constants, which are going from genetic base and his individual developing. Really important and actual, this way open new forms in the fields of musicological analyze. Main objective of the study. Studying to composer’s instrumental music and its stylistic specifications (as an example H. Liashenko’s Concert for Harp and strings), we’re seeing they roots in his mental and world viewing constants, widely cultural and psychological preferences. Methodology As the method of study is complex analyze, which open the deep levels of his creative process. How the study was done. As the still of specifies by Liashenko’s creative meanings, his personal and scientific mentality, spiritual and social states was analyzed as crossing by. In the same analytic way we’re seeing some common connections between his technological disciplines such as «canon». Results and conclusions. As a result, H. Liashenko constructed his own individual views of form building and about music materiel’s development with the help of some «author signs» We note them as the new text elements (neologism), full of metaphorical senses and which shows some varieties’ potential. In this Concert for Harp and Strings their contain and dramaturgical functions are rich. Practical significance. The studying of musical piece (and completely, mechanism of composer creation) by this way were opened the deep roots and narratives about individual means in composer’s creative process.